Perencanaan Pendidikan Tinggi Dakwah Islam - Kusnawan, Aep (Jurnal Ilmu Dakwah, 2010)
Its essensial, planning constitute set of activity process to prefare decision of what happened occure. Planning in high education of Islamic daâwah worldÂ  placement strategy in all education process that apllied and give clear direction in all effortsÂ Â  of Islamic daâwah high education process. Through planning, management of education efforts will implemented as effective and efficient. The ducation planning also hopped will give positive effectÂ  inÂ  increasing the quality of Islamic daâwah high education. Therefore, to regulate planning not in estimate, manipulate or theory without fact. That prefaring of plan need maturity and need for assessment, By this, planning be clear in steps, model, component, process and its kind.